Ketentuan Adat Alas Di Aceh Tenggara Tentang Perkawinan Semarga - Fitrah, Jariatun; Astuti, Mirsa (EduYustisia, 2024)
Every society throughout the world has a legal system within its territory. There is no nation that does not have a national legal system. A nation's national law is a reflection of the culture of the nation concerned. Because law is the nation's mind and grows from the nation's legal awareness, the law will appear as a reflection of the nation's culture. The research method used is normative juridical research, namely legal research carried out by examining library materials or secondary data. In Alas society, it is known that there is an ideal marriage based on mate restrictions which causes people to have to marry outside certain environmental boundaries (exogamy). In Alas society, there is a prohibition against marrying within the clan. Sanctions given to perpetrators of same-marga marriages are expulsion from customs, from clan groups, neighborhood associations and even exile from the area where perpetrators of same-marga marriages live. The Alas community in Lawe Bulan District hopes that every citizen of the Alas community can respect, protect, uphold and follow every customary provision that applies in the Alas custom so that the values and characteristics of the Alas custom itsel